CREATIVE SEARCH OF CHINESE PAINTERS OF THE SECOND HALF OF THE 20th CENTURY: WU GUANZHUN, ZHU DEQUN, ZAO WU-KI - ЧЖУ, Ц. (Art and Design, 2023)
Goal: the purpose of the article is to highlight the principles of combining the approaches and techniques of Western and Chinese painting on the example of artworks of artists of the second half of the 20th century (Wu Guanzhong, Zhu Dejun and Zao Wu-Ki). Methodology. Research methods are determined by the specifics of the material and tasks. The author applied biobibliographical method of research, as well as techniques and methods of comparative, formal, figurative and stylistic analysis. Results. The article describes features of cultural and political processes in China in the 20th century. It outlines the main directions and essence of discussions about the ways of development of society and the tasks of art as well as their influence on the formation of aesthetic education concept. It has been established that representatives of the so-called “Parisian School” Wu Guanzhong, Zhu Dequn and Zao Wu-Ki are among the painters who most consistently mastered Western painting and received recognition both in China and abroad. The article analyzes biographical and visual materials; it is shown that the formation of these people as artists and their creative activity took place against the backdrop of the dizzying events of the 20th century and was largely determined by them. The main approaches to mastering the European system of painting, ways of creative interpretation of the Chinese tradition and achievements are reflected on the basis of the analysis of paintings by Wu Guanzhong, Zhu Dequn and Zao Wu-Ki. Scientific novelty. Representative works of three artists were collected, systematized and identified, their formal and figurative-stylistic analysis was carried out and highlighted. The practical significance of the results of the study lies in the possibility of their use in pedagogical work in the development of programs and methodological materials for Art History courses and in practical work of artists.